Efficiency analysis of BLDC motor for variable magnetic field - Yıldırım Özüpak (MANAS: Journal of Engineering)
With the developing technology, direct current motors have been widely used in industrial applications. The limited use of brushed models in some areas has made Brushless Direct Current Motors stand out. In this paper, the design and analysis of an efficient, high power density, brushless direct current motor (BLDC) for use in electric vehicles is carried out. In this direction, studies have been carried out to reduce the reverse induced voltage, which is the biggest problem of electric motors in the electric vehicle sector. Analyzes were carried out with ANSYS subprograms, which realized a Finite Element Method (FEM) based solution to change the nominal values of the BLDC motor by changing the distance between the rotor and the stator. According to the results of the analysis, it was concluded that the method used in the study can also be used in high speed applications of brushless direct current motors.